A simple fabrication process for SiNx/SiO2 waveguide based on sidewall oxidation of patterned silicon substrate. Issue 3 (4th February 2017) - Wang, Ya'nan; Luo, Yi; Xiong, Bing; Sun, Changzheng; Wang, Jian; Hao, Zhibiao; Han, Yanjun; Wang, Lai; Li, Hongtao
Abstract : A novel and efficient fabrication process based on sidewall oxidation of patterned silicon substrate is proposed and experimentally demonstrated for SiN x /SiO 2 waveguides on silicon substrate. The fabrication time of a 5.5 μ m-thick lower SiO 2 cladding formed by the proposed sidewall oxidation method is only 1/3 of that required by conventional flat surface oxidation process. Thermal annealing process is carried out to reduce the propagation loss of the waveguide due to material absorption in the SiN x core and the SiO 2 upper cladding formed by plasma enhanced chemical vapour deposition. Furthermore, it is confirmed that waveguides fabricated by sidewall oxidation exhibit similar propagation loss as those obtained with conventional surface oxidation process.